2014
DOI: 10.4103/0377-4929.130877
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between p16 expression and INK4a locus mutation with grades and stages in oral squamous cell carcinoma

Abstract: Loss of p16INK4a expression occurred in initial stages of oral squamous cell carcinoma. Evaluation of TS and CS for p16INK4a might be a useful clinical indicator concerning the tumor. However, gene mutation is believed to have minor rate of genetic alteration in carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
4
1
Order By: Relevance
“…[ 22 ] Sargolzaei et al found that expression of p16 was 33.3%, 31.6% and 33.3% in WDSCC, MDSCC and PDSCC which were consistent in all grades when compared to our findings. [ 6 ] In contrast to this study, Mahale and Saranath found 83% positivity in PDSCC as compared to 46% of MDSCC to WDSCC. [ 16 ] Tsai et al found an elevation in histological grades showing 54% in WDSCC, 56.5% in MDSCC and 58% in PDSCC.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…[ 22 ] Sargolzaei et al found that expression of p16 was 33.3%, 31.6% and 33.3% in WDSCC, MDSCC and PDSCC which were consistent in all grades when compared to our findings. [ 6 ] In contrast to this study, Mahale and Saranath found 83% positivity in PDSCC as compared to 46% of MDSCC to WDSCC. [ 16 ] Tsai et al found an elevation in histological grades showing 54% in WDSCC, 56.5% in MDSCC and 58% in PDSCC.…”
Section: Discussioncontrasting
confidence: 85%
“…Sargolzaei et al found expression of p16 higher in Stage I compared to Stage II–IV. [ 6 ] Our study showed higher positivity in Stage 2 OSCC cases. Hiroshi et al found LOH at chromosome 9p and suggested that LOH at chromosome 9p could be detected in early stage and the frequencies of LOH tend to be higher in later clinical stages.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations